2017
DOI: 10.1177/2309499016684750
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous healing of lateral femoral cutaneous nerve injury and improved quality of life after total hip arthroplasty via a direct anterior approach

Abstract: Purpose: How the symptomatology of lateral femoral cutaneous nerve (LFCN) injury changes after total hip arthroplasty (THA) via direct anterior approach (DAA) is not known. Our hypothesis was that the symptoms of LFCN injury after THA via DAA in longer follow-up periods would resolve spontaneously, leading to an improved quality of life (QOL). The aims of this study were to investigate how the symptom LFCN injury changed after DAA-THA, and how those changes affected QOL. Methods: We investigated the incidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 21 publications
3
16
1
Order By: Relevance
“…Several reports have stated that LFCN injury does not affect hip joint function after THA (6,20,21). Indeed, the presence of LFCN injury did not affect improvement in joint function in our previous study (22). In the same group of patients, however, we demonstrated that LFCN injury reduced the QOL after surgery (10,22).…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…Several reports have stated that LFCN injury does not affect hip joint function after THA (6,20,21). Indeed, the presence of LFCN injury did not affect improvement in joint function in our previous study (22). In the same group of patients, however, we demonstrated that LFCN injury reduced the QOL after surgery (10,22).…”
Section: Discussionsupporting
confidence: 41%
“…Indeed, the presence of LFCN injury did not affect improvement in joint function in our previous study (22). In the same group of patients, however, we demonstrated that LFCN injury reduced the QOL after surgery (10,22). Therefore, we believe that reducing LFCN injury is essential for improving the outcome of THA using the DAA.…”
Section: Discussionmentioning
confidence: 56%
“…21 , 24 Critics claim that safety and efficacy of MIS have yet to be determined. 22-23 Frequently in combination with MIS THA, different types of short femoral stems, commercially available, preserve more femoral bone and make a possible revision surgery, in the future, less complicated. These advantages may simplify even more a simultaneous bilateral THA.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several studies have also reported that the MIS-THA significantly reduced postoperative pain and led to faster postoperative rehabilitation when compared with the respective traditional approaches. 22-29 In addition, a simultaneous bilateral one stage MIS-THA (1-MIS-BTHA) with either anterolateral or direct anterior approach could be performed in supine position which may facilitate the surgeon to operate on the contralateral side without the necessity of changing the patient’s position (in contrast to the posterior approach). Therefore, MIS-THA could be the most suitable operative technique for the better outcome in the patients undergoing 1- BTHA.…”
Section: Introductionmentioning
confidence: 99%
“…Also, compared with the greater trauma of the conventional approach, minimally invasive surgery cannot be de ned by short incision solely. For instance, direct anterior access may injury the lateral femoral cutaneous nerve [24]; lateral approach may injure the superior gluteal nerve and cut off the insertion of gluteus minimus [25]; the posterior lateral approach needed to cut the piriformis muscle and then expose joint capsule [26]. In terms of minimally invasive surgery, the SuperPATH technology was a true minimally invasive technique.…”
Section: Discussionmentioning
confidence: 99%